2011
DOI: 10.1088/2058-7058/24/01/44
|View full text |Cite
|
Sign up to set email alerts
|

Our quantum-entangled marriage

Abstract: It all began rather innocuously. Right from the start, Natalie and I had a lot in common. We both liked to travel. We both enjoyed sailing. And we both tended to listen to rock music played a little too loudly. Then, after we got married a few years later, it became more noticeable. We started buying our clothes in the same shops. We shared books after we had finished reading them. I even started to do the ironing without being asked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…But in 1985, Graham Hutchings from the University of Cardiff, UK reported that the gold ions could catalyze the hydrochlorination reaction. Similarly, Masatake Haruta, from Tokyo Metropolitan University in Japan, later observed that in NP form gold could catalyze oxidation of carbon monoxide even at low temperatures of -76°C 19 . In recent years there has also been increasing interest in the use of silver NPs as antimicrobial agents.…”
Section: Historical Perspectivementioning
confidence: 93%
See 2 more Smart Citations
“…But in 1985, Graham Hutchings from the University of Cardiff, UK reported that the gold ions could catalyze the hydrochlorination reaction. Similarly, Masatake Haruta, from Tokyo Metropolitan University in Japan, later observed that in NP form gold could catalyze oxidation of carbon monoxide even at low temperatures of -76°C 19 . In recent years there has also been increasing interest in the use of silver NPs as antimicrobial agents.…”
Section: Historical Perspectivementioning
confidence: 93%
“…The first evidence of metallic nanoparticles is from 2000 years ago when gold NPs were a part of ancient ayurvedic medicine in India 19 . 56 nm sized colloidal gold NPs, also called the swarna bhasmaI (gold ash) was mixed with honey or cow ghee and given orally to patients to treat a wide range of diseases including rheumatoid arthritis, bronchial asthma, diabetes mellitus and other diseases of the nervous system 19, 20 . The aesthetic property of gold NPs was later realized and exploited by the Romans.…”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, natural compounds are treasure troves for synthetic organic chemists and drug discovery researchers. 4 The oldest medical text comes from Mesopotamian ancestors, who described ca. 1000 plants, such as Commiphora myrrha, Papaver somniferum, and Cedrus sp, as being useful remedies.…”
Section: Introductionmentioning
confidence: 99%
“…However, they reduce food quality and value. Therefore, discovering these frauds represents a continuous challenge in the analytical field 3.…”
Section: Introductionmentioning
confidence: 99%